Synthesis of TRIPCO: A New Cyclooctyne for iSPAAC - Lis, Christian; Berg, Thorsten (Synlett, 2019)
Strain-promoted azide–alkyne cycloadditions (SPAAC) are widely used for labeling azide-functionalized biomolecules in living cells but create mixtures of isomeric triazoles. We recently expanded the scope of SPAAC to the isomer-free generation of large functional molecules in living cells by designing the symmetrical pyrrolocyclooctynes PYRROC and SYPCO, which do not form isomers in SPAAC. Here, we present the synthesis and kinetic characterization of the cyclooctyne TRIPCO as a new reagent for isomer-free SPAAC (iSPAAC). TRIPCO was found to react faster than PYRROC and SYPCO in the [3+2] cycloaddition with benzyl azide.
Keywords: bioorthogonal chemistry; cycloalkynes; isomer-free SPAAC; cycloaddition; azides